Membrane filtration - the effect of turbulence - Chong, Joseph Xuefeng (2015)
Membrane biotechnology is continually improving as the industry seeks new ways to further improve the efficiency of methods and also reduce costs. The current industry uses aeration to reduce fouling of hollow fiber membranes so as to prolong its operation before any maintenance is required. However, there is an increase in the study of how generating turbulence with the means of vibration can provide a more efficient and cost saving solution. In this study, the membrane module was fixed onto a mounting bracket and a vibrating grid is placed underneath to generate turbulence. The grid had a solidity of 66.67% with 1cm circular holes. 16 Polyacrylonitrile(PAN) hollow fiber membranes were attached onto the membrane module in each experiment. A Particle Imaging Velocimetry(PIV) system was also implemented to help quantify the turbulence generated into turbulent kinetic energy (k) , longitudinal and transverse integrated length scale (l) parameters. The results showed that the 16mm amplitude used (largest amplitude) helped to reduce the speed of the buildup of TMP. This was also found to be correlated to the k values which also showed that at 16mm amplitude, the turbulence generated amongst the other amplitudes was the highest. Higher frequencies (up to 4Hz) were also found to help reduce the rate of membrane fouling. The Longitudinal l values obtained showed that as the frequency increased, the turbulence generated through the integrated length scale also increased. The most interesting aspect of the study was that the reduced membrane fouling that took place at higher elevations was shown to not necessary be caused by higher concentrations of mixed liquor suspended solids (MLSS) as previously thought. The Longitudinal l values indicated that the peak turbulence generated was at about 6 or 7cm elevation which was similar to that of the TMP data. The purpose of the study was to gain a better understanding as to how turbulence could ultimately affect membrane fouling in terms of the parameters k, Ll and Lt. A correlation was done between the three different turbulence parameters and the rate at which fouling occurred (dTMP/dt). Through the correlation, an equation was developed to aid quantifying and predicting the rate of membrane fouling. The equation (dTMP/dt=C_1 k^(-1.935) L^(-1.049)) would act as a guide for further progress in this field.